2021
DOI: 10.1182/blood.2020007140
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic enzyme pyruvate kinase M2 regulates platelet function and arterial thrombosis

Abstract: Very little is known about the role of metabolic regulatory mechanisms in platelet activation and thrombosis. Dimeric pyruvate kinase M2 (PKM2) is a crucial regulator of aerobic glycolysis that facilitates the production of lactate and metabolic reprogramming. Herein, we report that limiting PKM2 dimer formation, using a small molecule inhibitor ML265, negatively regulates lactate production and glucose uptake in human and murine stimulated platelets. Furthermore, limiting PKM2 dimer formation reduced agonist-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…4 F, right). TEPP-46, a small molecule inhibitor, could limit PKM2 dimer formation [ 32 , 33 ]. We found that TEPP-46 was sufficient to reverse the GTPBP4-overexpression-mediated ECAR increase in GTPBP4 OE PLC/PRF/5 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 F, right). TEPP-46, a small molecule inhibitor, could limit PKM2 dimer formation [ 32 , 33 ]. We found that TEPP-46 was sufficient to reverse the GTPBP4-overexpression-mediated ECAR increase in GTPBP4 OE PLC/PRF/5 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PKM2 is a central regulator of aerobic glycolysis of cancer cells, which accelerates lactate production as well as metabolic reprogramming [ 21 ]. Our western blotting showed that 200 μ M Sal B-treated NCI-H2030 and NCI-H1650 cells displayed remarkably reduced expression of PKM2 and p-PKM2 in comparison to controls (Figures 4(a) – 4(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…For the FeCl 3 -induced thrombosis model, exogenous carboxyfluorescein succinimidyl ester (CFSE)–labeled platelet was infused into the tail vein. Mice were anaesthetized using 1% pentobarbital, then the common carotid artery was carefully exposed and kept moist by super-fusion with warm (∼37°C) saline, a filter paper (5 × 3 mm) saturated with 5% ferric chloride (FeCl 3 ) solution was applied topically for 1 min, the thrombus formation in the injured carotid vessel was monitored using a Nikon A1RMP + Two-Photon Microscope ( Nayak et al, 2021 ), Time to occlusion exceeding 30 min was noted as 30 min. The time to form occlusive thrombus was considered as the time required for blood to stop flowing completely for >1 min.…”
Section: Methodsmentioning
confidence: 99%